The Quest for Citations: Drivers of Article Impact - Stremersch, Stefan; Verniers, Isabel; Verhoef, Peter C. (Journal of Marketing, 2007)
Why do some articles become building blocks for future scholars, whereas others remain unnoticed? The authors aim to answer this question by contrasting, synthesizing, and simultaneously testing three scientometric perspectives—universalism, social constructivism, and presentation—on the influence of article and author characteristics on article citations. They study all articles published in a sample of five major journals in marketing from 1990 to 2002 that are central to the discipline. They count the number of citations each of these articles has received and regress this count on an extensive set of characteristics of the article (i.e., article quality, article domain, title length, the use of attention grabbers, and expositional clarity) and the author (i.e., author visibility and author personal promotion). They find that the number of citations an article in the marketing discipline receives depends more on “what is said” (quality and domain) and “who says it” (author visibility and personal promotion) than on “how it is said” (title length, the use of attention grabbers, and expositional clarity). The insights gleaned from this analysis contribute to the marketing literature and are relevant to scientific stakeholders, such as the management of scientific journals and individual academic scholars, as they strive to maximize citations. They are also relevant to marketing practitioners; they inform practitioners on characteristics of the academic journals in marketing and their relevance to decisions they face. Conversely, the insights also raise challenges regarding how to make journals accessible and relevant to marketing practitioners: (1) Authors visible to academics are not necessarily visible to practitioners; (2) the readability of an article may hurt academic credibility and impact, but it may be instrumental in influencing practitioners; and (3) it remains questionable whether articles that academics assess to be of high quality are also managerially relevant.